(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tourism is becoming more and more recognised as a way for the country to create jobs and grow. It is important to know what tourism is, what role it plays in the economy, and how it relates to other parts of the economy. Tourism is becoming more and more important around the world, and governments are putting in place policies to encourage it. This has sped up the growth of the tourism industry in a big way. India’s tourism receipts are second only to manufacturing in terms of their share of total exports. This shows how important tourism is as an export-led growth strategy. In the last ten years, research on how to measure how much tourism helps the economy has grown quickly. The reasons are easy to understand: in many countries, tourism is seen as a magic bullet for economic growth, and governments need a reliable measurement tool to come up with national and local plans for boosting tourism development. The goal of this study is to come up with smart and creative ways to promote tourism in India in order to boost long-term economic growth and global trade.